Serotonin syndrome following metaxalone overdose and therapeutic use of a selective serotonin reuptake inhibitor. (March 2015) - Martini, Dyllon Ivy; Nacca, Nicholas; Haswell, David; Cobb, Timothy; Hodgman, Michael
Abstract Metaxalone has only recently been associated with serotonin syndrome. The mechanism of action of this centrally acting muscle relaxant is unknown; however, the observation of serotonin syndrome in patients with metaxalone overdose suggests a role in the serotonergic pathway. Case report. (Case 1) A 29-year-old woman with overdose of metaxalone presented to the emergency department with altered mental status, seizure-like activity, hyperthermia, rigidity in the lower extremities, myoclonus, and hyperreflexia. Vital signs on arrival include blood pressure of 168/80 mmHg, heart rate of 208 beats per minute (bpm), respirations of 20/min, a temperature of 41.6° C rectally, and room air oxygen saturation of 97%. She was intubated and sedated with benzodiazepines, and actively cooled. Serum paroxetine concentration was 23 (therapeutic range: 20–200) ng/mL, and serum metaxalone concentration was 31 mcg/mL (peak plasma concentrations average 0.9 mcg/mL at 3.3 h following a single oral dose of 400 mg). (Case 2) A 27-year-old man presented to the emergency department with altered mental status, rigidity in his lower extremities, myoclonus, and hyperreflexia. Vital signs on arrival include blood pressure of 158/131 mmHg, heart rate of 126 bpm, respiratory rate of 20 breaths per minute, and temperature of 37.2°C, with oxygen saturation of 98% on room air. His medication list included metaxalone and escitalopram. He was managed aggressively with IV boluses of diazepam, in total 80 mg, in the emergency department. Serum escitalopram concentration was 24 ng/mL with a therapeutic range of 21–64 ng/mL, and serum metaxalone concentration was 58 mcg/mL. Conclusion. These two cases suggest that at supratherapeutic concentrations metaxalone has serotonergic effects. Severe serotonin toxicity may result from metaxalone abuse in individuals using a selective serotonin reuptake inhibitor therapeutically.